2016
DOI: 10.21577/0103-5053.20160235
|View full text |Cite
|
Sign up to set email alerts
|

Fast Sample Preparation Method Using Ultra-High Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry for Natamycin Determination in Wine Samples

Abstract: An easy and efficient sample preparation method was developed for the determination of natamycin residues in wine samples by solvent extraction and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) analysis. After choosing acetonitrile as extraction solvent, an experimental design was carried out with different amounts of C18 and primary secondary amine (PSA) sorbents in order to optimize the clean-up step. Validation results were satisfactory, with recoveries from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, Brasil (2017) establishes that the use of alternative approaches for the validation of analytical methods applied to biological products will be admitted and that the use of a method with technical limitations to determine selectivity is accepted through technical justification. In this regard, Bernardi et al, (2016);Yang et al, 2015) demonstrated that the sample dilution (dilution factor 15 to 100) before injection into the LC-ESI MS/MS system is an easy and effective method to improve the selectivity of the method and to reduce or eliminate the matrix effect (effect on the analytical response induced by interfering compounds present in the matrix) (Bernardi et al, 2016). Thus, in this study, selectivity and elimination of the possible matrix effect was assessed by the dilution approach, since depending on the matrix and the analyte the samples were diluted (ranged between 10 to 400 times) to get in the linear range of the analytical curves.…”
Section: Resultsmentioning
confidence: 98%
“…However, Brasil (2017) establishes that the use of alternative approaches for the validation of analytical methods applied to biological products will be admitted and that the use of a method with technical limitations to determine selectivity is accepted through technical justification. In this regard, Bernardi et al, (2016);Yang et al, 2015) demonstrated that the sample dilution (dilution factor 15 to 100) before injection into the LC-ESI MS/MS system is an easy and effective method to improve the selectivity of the method and to reduce or eliminate the matrix effect (effect on the analytical response induced by interfering compounds present in the matrix) (Bernardi et al, 2016). Thus, in this study, selectivity and elimination of the possible matrix effect was assessed by the dilution approach, since depending on the matrix and the analyte the samples were diluted (ranged between 10 to 400 times) to get in the linear range of the analytical curves.…”
Section: Resultsmentioning
confidence: 98%